A REVIEW STUDY ON MOBILE PHONES VS BASIC AMENITIES IN THE INDIAN URBAN SLUMS DWELLERS - kumar.ch, Dr. Subha; Marapatla, Dr. Gangayya (IJRDO - Journal of Applied Management Science, 2017)
Needless to say, cell phones are part of our everyday life. But, the more overpoweringquestion, as with every invention in our civilized world, is if there is a downside to our progress, andmore specifically what levels of health problems has our use of the cell phone brought to our doorstep?On the surface of harmful cell phone use, is its potential to permanently damage brain cells throughcellular phone frequencies. Believe it or not, science does not have a clear consensus on this issue.Instead of sounding a warning bell of despair, let’s look at both sides of the argument to uncover theissues surrounding this topic. In this research paper we studied about Basic amenities Vs Cell phonesin India half of India’s homes have cell phones, but not toilets Census sheds new light on changingnation . These and many other contrasting facts of life have come out in Census 2011. The data onhousing, household’s amenities and assets cast new light on country in the throes of complextransition where millions have access to state-of art technologies and consumer goods – but a largernumber of lacks access to the most rudimentary facilities in the urban slums the Andhra Pradeshurban slums.